Need for Prioritizing Health: An Old War-Cry Reiterated By COVID-19 - Shrestha, Rijen; Nepal, Samata; Atreya, Alok (Journal of Lumbini Medical College, 2020)
The poor state of health care in Nepal will be burdened further following the SARS-CoV-2 pandemic. The government failed in timely stockpiling of medical supplies and equipment, development of health infrastructure, including laboratories and quarantine centres, restriction and screening of international travel and information dissemination to the general public. While efforts have now been made to increase the capacity for diagnostic test for SARS-CoV-2, the government still needs to further increase the availability and accessibility throughout the country. This would be the first step in fighting the pandemic. However, it is also important to prepare for the worst case. Similarly, advocacy programs should be developed to inform the general public and alleviate their fears about the disease. These measures would not only help Nepal’s capability to respond to the COVID-19 outbreak but could lay the foundations to improve the health of the citizens in general, even after this epidemic is controlled and could go a long way in developing trust of the government in the populace.